Manufacture of Rotationally Symmetric Multilayer Refractory Devices for Steel Casting Applications by Spiral Winding of Ceramic Green Tapes - Jakobsen, Björn Daniel; Hammerbacher, Ruth; Dudczig, S.; Fey, Tobias; Roosen, Andreas (Journal of Ceramic Science and Technology, 2014)
In order to create rotationally symmetric refractory devices from ceramic green tapes, the spiral winding method, which is mainly known from the paper industry, was applied. Different green tapes with varying properties with regard to shrinkage, porosity and Young's modulus were used to generate multilayer tubes with the spiral winding and the cold low pressure lamination technique. The tubes were fired in air and their microstructure was investigated. Thermal shock tests were conducted to evaluate the applicability of the fabricated structures for refractory applications. The correlation between the microstructure and thermal shock behaviour of the tubes is discussed.
Keywords: Spiral winding; green tapes; refractories; thermal shock